Metabolic changes in serum steroids for diagnosing and subtyping Cushing's syndrome. Issue 210 (June 2021) - Ahn, Chang Ho; Lee, Chaelin; Shim, Jaeyoon; Kong, Sung Hye; Kim, Su-jin; Kim, Yong Hwy; Lee, Kyu Eun; Shin, Chan Soo; Kim, Jung Hee; Choi, Man Ho
Abstract: To evaluate the diagnostic value of serum levels of adrenal steroids for diagnosing and subtyping Cushing's syndrome. Patients diagnosed with endogenous Cushing's syndrome (34 and 19 patients with adrenal and pituitary Cushing's syndrome, respectively) and healthy controls (n = 34) were consecutively enrolled at Seoul National University from 2016 to 2020. Morning serum samples were collected before and 3 months after treatment. Serum steroids were profiled using liquid chromatography-mass spectrometry. The diagnostic value of each and the combination of steroids were assessed using the area under the curve of receiver operating characteristic (AUROC) and decision tree analysis. Tetrahydrocortisone and 6β-hydroxycortisol showed the highest AUROC (0.893 and 0.890, respectively) for the diagnosis of endogenous Cushing's syndrome. The decision tree composed of tetrahydrocortisone and 6β-hydroxycortisol correctly classified 79/87 (90.8 %) subjects. For subtyping into adrenal or pituitary Cushing's syndrome, dehydroepiandrosterone sulfate (DHEA-S) showed the highest AUROC (0.988), which was similar to that of plasma ACTH (0.994, P = 0.458). The decision tree composed of only DHEA-S correctly classified 51/53 (96.2 %) of the Cushing's syndrome subtype. DHEA-S showed a significant linear correlation with the plasma ACTH level, but not with the 24 -h urine free cortisol or dexamethasone suppression test results. All steroids, except allo-tetrahydrocortisol and tetrahydrocortisone, decreased significantly at 3 months post-treatment with similar patterns in both adrenal and pituitary Cushing's syndrome. Serum steroid profiling using a single morning serum sample provides valuable information for diagnosing and subtyping Cushing's syndrome.